2019
DOI: 10.1111/nph.15924
|View full text |Cite
|
Sign up to set email alerts
|

Sensing β‐carotene oxidation in photosystem II to master plant stress tolerance

Abstract: Stressful environmental conditions lead to the production of reactive oxygen species in the chloroplasts, due to limited photosynthesis and enhanced excitation pressure on the photosystems. Among these reactive species, singlet oxygen ( 1 O 2 ), which is generated at the level of the PSII reaction center, is very reactive, readily oxidizing macromolecules in its immediate surroundings, and it has been identified as the principal cause of photooxidative damage in plant leaves. The two b-carotene molecules prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 84 publications
3
50
0
Order By: Relevance
“…On the other hand, H 2 O 2 and the β-CC-mediated 1 O 2 signaling pathways may converge at Oxidative Signal-Inducible 1 kinase [407,454]. β-CC also down-regulates SAL1 and up-regulates genes generating PAP [391,423], supporting the view that both H 2 O 2 -and β-CC-signaling pathways induce stress acclimation.…”
Section: Of 63mentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, H 2 O 2 and the β-CC-mediated 1 O 2 signaling pathways may converge at Oxidative Signal-Inducible 1 kinase [407,454]. β-CC also down-regulates SAL1 and up-regulates genes generating PAP [391,423], supporting the view that both H 2 O 2 -and β-CC-signaling pathways induce stress acclimation.…”
Section: Of 63mentioning
confidence: 78%
“…Accordingly, under severe stress, the β-CC pathway, through Oxidative Signal-Inducible 1 kinase, may also lead to PCD, but even this route is EX1-independent [421,422]. Most β-CC is produced from the β-carotene located in the RC of PSII [390,423], and therefore in the grana core [424], whereas EX1 is located in grana margins [425]. As 1 O 2 is not expected to diffuse far, the site of production rather than the amount may determine which signaling pathway is activated.…”
Section: Signaling By 1 Omentioning
confidence: 99%
“…During the last 15 years, studies performed mainly in Arabidopsis thaliana have revealed a complex network of signals that allows chloroplasts to communicate their functional status to the nucleus. Singlet oxygen [ 108 ], H 2 O 2 [ 109 ], the redox state of the photosynthetic electron transport chain [ 110 ], 3′-phosphoadenosine 5′-phosphate [ 111 ], the isoprenoid precursor methylerythritol cyclodiphosphate [ 112 ], β-cyclocitral [ 113 , 114 ] and other potential candidates [ 115 , 116 , 117 , 118 , 119 ] have been added to the list of operational control signals [ 107 ]. Understanding the degree to which these pathways are operative in monocot species like barley, together with a deeper knowledge of the regulatory, biochemical and redox networks that control the stability, functionality and disassembly of the photosynthetic apparatus under stress conditions and during induced senescence is pivotal for the identification of novel genes and favourable allelic variants for use in breeding programs.…”
Section: Barley Is Ready For a New Age Of Functional Genomics Studmentioning
confidence: 99%
“…Oxidation of the carotenoid β-carotene by reactive oxygen species (ROS), especially singlet oxygen ( 1 O 2 ), produces various derivatives (apocarotenoids) including β-cyclocitral (β-CC) (D’Alessandro and Havaux, 2019, Ramel et al., 2012a, Ramel et al., 2012b, Shumbe et al., 2014). This phenomenon was shown to take place in plant leaves and to be enhanced under stress conditions (Ramel et al., 2012a, Ramel et al., 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…1 O 2 quenching by carotenoids proceeds by a physical mechanism that leads to thermal energy dissipation (Ouchi et al., 2010) and through a chemical quenching mechanism involving direct oxidation of the carotenoid molecule by 1 O 2 (Stratton et al., 1993, Ramel et al., 2012b, Pinnola and Bassi, 2018). Thus, as a major site of 1 O 2 production, PSII is also a major generator of oxidized β-carotene metabolites such as β-CC (D’Alessandro and Havaux, 2019).…”
Section: Introductionmentioning
confidence: 99%